Serdexmethylphenidate/dexmethylphenidate effects on sleep in children with attention-deficit/hyperactivity disorder - Mattingly, Greg W.; Childress, Ann C.; Cutler, Andrew J.; Estrada, José; Corliss, Meg (Frontiers in Psychiatry, 2023)
Introduction: Sleep-related problems are common in children with attention-deficit/hyperactivity disorder (ADHD). Sleep disorders are also side effects of all stimulant ADHD medications. Serdexmethylphenidate/dexmethylphenidate (SDX/d-MPH) is a once-daily treatment approved for patients age 6 years and older with ADHD. In this analysis, sleep behavior was assessed during SDX/d-MPH treatment in children with ADHD. Methods: In a 12-month, dose-optimized, open-label safety study in 6 to 12-year-old participants (NCT03460652), a secondary endpoint was assessment of sleep behavior based on the Children’s Sleep Habits Questionnaire (CSHQ) consisting of 8 sleep domains (bedtime resistance, sleep onset delay, sleep duration, sleep anxiety, night wakings, parasomnias, sleep-disordered breathing, and daytime sleepiness). This post hoc analysis examined the individual sleep domains in the 12-month safety study. Results: Of 282 participants enrolled, 238 were included in the sleep analysis. At baseline, mean (SD) CSHQ total sleep disturbance score was 53.4 (5.9). After 1 month of treatment, the mean (SD) CSHQ total score significantly decreased to 50.5 (5.4); least-squares mean change from baseline was −2.9 (95% CI: −3.5 to −2.4; p < 0.0001) and remained decreased up to 12 months. Mean sleep-score improvements from baseline to 12 months were statistically significant (p < 0.0001) for 5 of 8 sleep domains, including bedtime resistance, sleep anxiety, night wakings, parasomnias, and daytime sleepiness. Parasomnias and daytime sleepiness sleep domains showed the greatest mean improvement from baseline to 12 months. Sleep onset delay and sleep duration scores increased from baseline to 12 months. No statistically significant worsening occurred from baseline in sleep duration and sleep-disordered breathing domains; however, worsening of sleep onset delay was statistically significant. Conclusion: In this analysis of children taking SDX/d-MPH for ADHD, sleep problems did not worsen based on the mean CSHQ total sleep disturbance score. Statistically significant improvements in most CSHQ sleep domains were observed after 1 month and lasted for up to 12 months of treatment.